56 MicroRNAs 99b, 181a and 181b are induced during human embryonic stem cell differentiation to vascular endothelial cells and can enhance differentiation capacity upon differentiation. Issue 20 (23rd September 2011) - Kane, N M; Howard, L; Khanin, R; McClure, J; Breen, C; Milligan, G; Baker, A H
Abstract : Rationale: MicroRNAs (miRNAs) are short non-coding RNAs, which post-transcriptionally regulate gene expression. miRNAs are important in governing cell differentiation, development and disease. However, there is relatively little evidence demonstrating a functional role for miRNA in early human development of vascular cells, how they control endothelial cell (EC) fate commitment and the mechanisms involved in these differentiation processes. Methods and Results: Human embryonic stem (hES) cells were differentiated to ECs. Loss of miRNA processing by knockdown of DICER1 suppressed hES-EC differentiation. We next performed a miRNA microarray to screen hES-EC miRNA profiles during defined early stages of differentiation and identified several miRNAs expressed in a time and differentiation-dependent manner, namely miR99b, miR181a and miR181b. Expression of the aforementioned miRNAs in hES-EC cells was equivalent to the level in adult venous ECs. miRNA 99b, 181a and 181b overexpression potentiated expression of EC-specific markers, Pecam1 and VE Cadherin at day 10 and 14 of differentiation, compared to controls, observed at both mRNA and protein levels. Conversely, knockdown did not suppress endothelial marker protein expression. Conclusion: These results indicate that miRNAs 99b, 181a and 181b may comprise a component of an endothelial-miRNA signature as evidenced by expression profiles in adult EC and hES-EC cells. These miRNAs are also capable of potentiating EC differentiation from pluripotent hES cells, but are not essential for successful EC differentiation. Further elucidation of the role of miRNAs in hES-EC differentiation will aid the development of new approaches for cardiovascular disease cell therapy.